Pengaruh Academic Burnout Terhadap Motivasi Belajar Mahasiswa - Maisyaroh, Siti; Kholisna, Titin (Psikodinamika: Jurnal Literasi Psikologi, 2024)
Learning success is a goal because of the learning process. To support the success of the learning process, namely motivation, stability, maintaining motivation is an important aspect so that the learning process runs well. However, the problem is that working students are not only required to complete learning assignments in lectures but also at work. So when these tasks come together it can cause physical and emotional fatigue (burnout). This research aims to determine the influence of physical and emotional conditions on working students. The method uses quantitative with a sample of 348 semester 5 to 7 students who underwent the lecture process while working using a purposive sampling technique. Through item validity testing with product moment academic burnout 40 items, and learning motivation 25 items, it was met with a correlation coefficient of  0.30, and found a reliability of 0.909 which means very high. Analysis of the results of the partial significance test shows a sig value of 0.005  0.05, meaning that there is an influence between academic burnout and learning motivation. This shows that academic burnout has an important role in learning motivation. Keys: academic burnout, learning motivation